A deep purification method for removing fluorine by by-product hydrochloric acid adsorption
Patent Information
- Application Number
- CN202611323494.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-09-29
AI Technical Summary
[0006]本发明的目的在于克服现有技术的上述不足,提供一种副产盐酸吸附除氟的深度净化方法,解决现有除氟吸附剂的锆或稀土活性中心以羟基桥、氧桥聚集或单齿弱配位方式负载,在氯化氢质量分数为20%~36%的副产盐酸中被质子化解聚而流失、开放位点被锆氧锆桥饱和、且高氟负载时以氟锆酸根形式脱附,致使经沉淀预处理后的副产盐酸中残余氟化氢无法被连续、可再生地深度脱除的技术问题
[0009]与现有技术相比,本发明具有以下有益效果。第一,本发明以不可被质子化的羟基偕双膦酸配体通过Zr–O–P键将四价锆单核锚定于耐酸多孔载体孔道内,并通过锆与膦酸基团的摩尔比使每个锆中心保留三个以上可被氟化氢取代的水或羟基配位位,使浓盐酸中以分子态存在的氟化氢直接对质子活化的锆位点发生取代而被捕获,氯离子因不能进入四价锆内界而不构成竞争,从而在氯化氢质量分数为20%~36%的副产盐酸中实现出口氟含量0.5mg/L以下的深度脱除,且产品酸中锆含量低于0.05 mg/L。第二,通过在线监测与累计氟锆摩尔比双阈值切换,在充分利用吸附容量的同时避免了高氟负载下氟锆酸根的生成与活性中心脱附,经50次吸附-再生循环后穿透容量保持率达96%。第三,碱液洗脱再生与稀盐酸活化构成的闭环使锆位点在活化态、载氟态与脱附态之间可逆转换,洗脱液中的氟以氟化钙形式回收、滤液回用,整个过程不向盐酸中引入硅、钙、硼、有机硅等新杂质,无需精馏,可连续运行,适用于对氟要求严格的回用场景。
Smart Images

Figure CN122828432A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of industrial by-product hydrochloric acid purification and fluorine-containing impurity removal, specifically relating to a deep purification method for by-product hydrochloric acid adsorption and fluorine removal. Background Technology
[0002] Fluorochemical products such as chlorofluorocarbons (CFCs), hydrofluorocarbons (HFCs), fluorinated aromatics, and fluorinated pesticide and pharmaceutical intermediates produce large amounts of hydrogen chloride as a byproduct during fluorine-chlorine exchange, fluorination, or chlorination. After absorption by water, this hydrogen chloride yields hydrochloric acid with a mass fraction of 20%–36%. This byproduct hydrochloric acid inevitably contains unreacted hydrogen fluoride, with a fluoride content typically in the range of 0.1%–2%. Pretreatment with calcium chloride, lime slurry, or siliceous materials can reduce the fluoride content to 10–200 mg / L. However, this residual fluoride level is still significantly higher than the requirements for reuse in pharmaceutical or food-grade chloride salt preparation, electronic-grade hydrochloric acid raw materials, non-ferrous metal refining, and metal surface treatment. As a result, this byproduct hydrochloric acid can only be downgraded for low-value applications or even disposed of as waste acid, leading to resource waste and environmental burden. Therefore, how to continuously and economically remove trace amounts of fluoride from the pretreated byproduct hydrochloric acid to below 1 mg / L is a key bottleneck for the high-value reuse of this byproduct hydrochloric acid.
[0003] Existing technologies for defluorinating byproduct hydrochloric acid mainly follow three routes: precipitation, extraction, and distillation. Patent application CN117602580A discloses a method for defluorinating fluorinated hydrochloric acid. This method involves adding a silica-based absorbent material, such as waste glass shavings, to the fluorinated hydrochloric acid to convert hydrogen fluoride into fluorosilicic acid. Then, calcium chloride solution is added dropwise to form calcium fluorosilicate precipitate, followed by filtration. The fluoride content of the filtered hydrochloric acid is approximately 20 ppm. To reduce it to below 1 ppm, further distillation at 110°C under normal pressure or vacuum distillation is required. This method is essentially a reaction precipitation method. The silica-based material is consumed by hydrogen fluoride and is non-renewable. New impurities such as dissolved silicon and calcium are introduced into the acid simultaneously. The reaction rate is low under trace fluoride conditions, requiring a large excess of reagent. Deep removal relies on energy-intensive distillation, making continuous operation impossible. Patent application CN106927423A discloses a method for defluorinating an acidic aqueous solution containing hydrofluoric acid. It involves extracting hydrogen fluoride with trialkylchlorosilane or a mixture of it and hexaalkyldisiloxane, followed by regeneration of the organic phase with an alkaline solution. The fluoride content after defluorination is 3.2–8.3 ppm, with an extractant-to-fluoride mass ratio as high as 10–50:1. Furthermore, the organosilicon reagent and its hydrolysis products inevitably enter the hydrochloric acid phase, resulting in complex liquid-liquid separation operations and difficulty in achieving a product acid concentration below 1 mg / L. Patent application CN114436216A discloses a method for separating and recovering a mixed acid of hydrofluoric acid and hydrochloric acid. It uses silica and alkali metal chlorides to convert fluoride into fluorosilicate precipitates, suitable for the separation and recovery of high-fluoride mixed acids. However, it also suffers from high reagent consumption and the introduction of silicon and alkali metal impurities for trace amounts of fluoride. Patent application CN105377751A discloses a method for purifying hydrogen chloride, which uses activated alumina to adsorb hydrogen fluoride from gaseous hydrogen chloride at 100-120°C. However, the alumina is non-renewable after being converted into aluminum fluoride, and the method is only applicable to gaseous hydrogen chloride. The liquid phase byproduct hydrochloric acid needs to be desorbed into a gas before absorption, resulting in high energy consumption.
[0004] Adsorption is considered an ideal route for deep defluorination due to its continuous operation and regenerable adsorbents; however, existing defluorination adsorbents are all developed for water systems. US Patent 4717554A discloses an adsorption treatment method for soluble fluoride, which adsorbs fluoride in fluoride-containing water at pH 2-7 using hydrated rare earth oxides or insoluble hydrated rare earth salts, followed by desorption and regeneration with an alkaline solution at pH 10-14. This method explicitly limits adsorption to pH 2-7, while hydrated rare earth oxides are rapidly dissolved in concentrated hydrochloric acid at pH less than 0, and tetravalent cerium is reduced to soluble trivalent cerium by chloride ions, making it unsuitable for use as a byproduct of hydrochloric acid. US Patent 20130274357A1 discloses a hybrid anion exchange resin impregnated with hydrated zirconium oxide. This resin confines hydrated zirconium oxide nanoparticles within the gel phase of a quaternary ammonium anion exchange resin for the removal of fluoride and arsenic from water. The specification states that dissolution occurs at pH below 3.0, and the quaternary ammonium groups are completely occupied by chloride ions in concentrated hydrochloric acid. The hydrated zirconium oxide exists as aggregates of hydroxyl and oxygen bridges. These bridges are protonated and polymerized in concentrated hydrochloric acid into soluble zirconium oxychloride species, leading to zirconium loss and capacity collapse. Patent application CN101773816B discloses a method for preparing zirconium-loaded zeolite for fluoride removal. It involves impregnating zeolite with zirconium oxychloride to obtain zirconium-loaded zeolite. The optimal adsorption pH is 5, and the saturated adsorption capacity is 6.96 mg / g. The silica-alumina framework of the zeolite undergoes dealumination and disintegration in concentrated hydrochloric acid. Patent application CN102641730B discloses a method for synthesizing a fluoride ion adsorption resin, which embeds lanthanum hydroxide in a hydrophilic polymer framework and is only applicable to neutral to weakly acidic aqueous solutions. Lanthanum hydroxide dissolves and is lost in concentrated hydrochloric acid.
[0005] Based on the above-mentioned existing technologies, there are two inherent understandings in this field regarding the deep removal of trace amounts of fluoride from by-product hydrochloric acid: First, fluoride in concentrated hydrochloric acid exists as undissociated hydrogen fluoride molecules and does not contain exchangeable fluoride ions, and the chloride ion concentration is as high as 6~10 mol / L. Therefore, adsorption mechanisms based on anion exchange or electrostatic attraction are considered unable to selectively capture fluoride in concentrated hydrochloric acid. Second, hydrated oxides of zirconium and rare earth elements, supported oxides, and metal centers weakly coordinated with carboxylic acid, amine, and other groups dissolve and are lost in concentrated hydrochloric acid. Therefore, adsorption methods are limited to water treatment scenarios with pH 2~7, and in the purification of by-product hydrochloric acid, only consumable precipitation, extraction, or distillation routes can be used. In other words, the root cause of the failure of existing technologies in concentrated hydrochloric acid systems has not been correctly attributed. The bonding between the active center and the framework in existing zirconium-loaded or rare earth-loaded adsorbents is depolymerized by protons in media with a pH less than 0. The open active sites are insufficient due to the saturation of zirconium-oxygen-zirconium bridges. Furthermore, when the fluorine load increases, the active centers desorb in the form of fluorozirconate, resulting in the inability to continuously and regenerately remove the residual hydrogen fluoride in the by-product hydrochloric acid after precipitation pretreatment. Summary of the Invention
[0006] The purpose of this invention is to overcome the above-mentioned shortcomings of the prior art and provide a deep purification method for adsorbing and removing fluoride from by-product hydrochloric acid. This method solves the technical problem that the zirconium or rare earth active centers of existing defluorination adsorbents are loaded in a hydroxyl bridge, oxygen bridge aggregated or monodentate weak coordination manner, and are lost due to proton depolymerization in by-product hydrochloric acid with a hydrogen chloride mass fraction of 20%~36%, open sites are saturated by zirconium-oxygen-zirconium bridges, and desorbed in the form of fluorozirconate ions when the fluoride load is high. As a result, the residual hydrogen fluoride in the by-product hydrochloric acid after precipitation pretreatment cannot be continuously and renewably removed in a deep manner.
[0007] To achieve the above objectives, the technical solution adopted in this invention is summarized as follows. Byproduct hydrochloric acid, pretreated by precipitation, with a hydrogen chloride mass fraction of 20%–36% and a fluorine content of 10–200 mg / L, is passed through an adsorption column filled with an acid-resistant defluorination adsorption material. Deeply defluorinated hydrochloric acid is obtained from the column outlet. This acid-resistant defluorination adsorption material consists of an acid-resistant porous support and a zirconic acid framework confined within its pores. The zirconic acid framework is formed by the coordination of tetravalent zirconium and phosphonic acid ligands through Zr–O–P bonds. The molar ratio of zirconium to phosphonic acid groups is 1:(1.6–2.4), and the phosphonic acid ligand is {1-hydroxy-2-[4-(2-hydroxy-2,2-diphosphonoethyl)phenyl]-1-phosphonoethyl}phosphonic acid. During operation, the fluorine content at the outlet of the adsorption column is monitored online. When the outlet fluorine content reaches the set threshold, or when the ratio of the cumulative amount of fluorine entering the adsorption column to the amount of zirconium in the column during the current adsorption cycle reaches 1.2:1, the by-product hydrochloric acid is switched to another adsorption column. The switched adsorption column is then recycled after being replaced with water, eluted and regenerated with a sodium hydroxide or potassium hydroxide solution with a concentration of 0.5~2 mol / L, washed with water, and activated with hydrochloric acid with a concentration of 0.5~2 mol / L.
[0008] In a preferred embodiment, the acid-resistant defluorination adsorbent material is prepared by first impregnating macroporous polystyrene-divinylbenzene microspheres with a hydrochloric acid-ethanol solution of zirconium oxychloride, then immersing them in an aqueous solution of phosphonic acid ligands at 60-95°C to generate a zirconic phosphonic acid framework in situ within the pores, followed by aging in 3-6 mol / L hydrochloric acid at 80-95°C and washing with water until the zirconium content in the washing solution is less than 0.1 mg / L. The mass fraction of zirconium in the material is 6%-12%. Furthermore, the aqueous solution of the phosphonic acid ligand also contains {2-[3,5-bis(2-hydroxy-2,2-bisphosphonoethyl)phenyl]-1-hydroxy-1-phosphonoethyl}phosphonic acid as a co-ligand, and the molar ratio of {1-hydroxy-2-[4-(2-hydroxy-2,2-bisphosphonoethyl)phenyl]-1-phosphonoethyl}phosphonic acid to {1-hydroxy-2-[4-(2-hydroxy-2,2-bisphosphonoethyl)phenyl]-1-phosphonoethyl}phosphonic acid is (0.1~0.3):1; the cured material can also be end-capped with a dilute hydrochloric acid solution containing {1-hydroxy-2-[4-(2-methylpropyl-2-yl)phenyl]-1-phosphonoethyl}phosphonic acid. In a preferred embodiment, the adsorption column uses at least two pre- and post-columns connected in series. The outlet of the pre-column is monitored online, and the switching threshold is set to 5% to 10% of the inlet fluoride content. The online monitoring is performed by automatic sampling, dilution to a hydrogen chloride concentration not exceeding 0.5 mol / L, buffering with acetic acid-sodium acetate to pH 5.0 to 5.5, and then measuring with a fluoride ion selective electrode. The alkaline solution also contains 0.2 to 2 mmol / L of sodium or potassium salt of {1-hydroxy-2-[4-(2-hydroxy-2,2-diphosphonoethyl)phenyl]-1-phosphonoethyl}phosphonic acid. Calcium fluoride is recovered by precipitation with calcium chloride at a calcium to fluoride molar ratio of (0.55 to 0.8):1. The filtrate is reused after alkali replenishment. After activation with hydrochloric acid, the feed is sequentially replaced with a gradient of 4 to 6 mol / L hydrochloric acid and deep defluorination hydrochloric acid before switching the feed.
[0009] Compared with existing technologies, this invention has the following advantages. First, this invention uses a non-protonable hydroxybisphosphonic acid ligand to anchor a tetravalent zirconium mononuclear site within the pores of an acid-resistant porous support via a Zr–O–P bond. By adjusting the molar ratio of zirconium to phosphonic acid groups, each zirconium center retains more than three water or hydroxyl coordination sites that can be replaced by hydrogen fluoride. This allows hydrogen fluoride, present in molecular form in concentrated hydrochloric acid, to directly substitute for and capture the proton-activated zirconium sites. Chloride ions, unable to enter the inner sphere of the tetravalent zirconium, do not compete for these sites. This achieves deep removal of fluoride from byproduct hydrochloric acid with a hydrogen chloride mass fraction of 20%–36% at the outlet, with a fluoride content below 0.5 mg / L, and a zirconium content in the product acid below 0.05 mg / L. Second, through online monitoring and dual-threshold switching of the cumulative fluoride-zirconium molar ratio, the invention fully utilizes the adsorption capacity while avoiding the formation of fluorozirconate ions and desorption from active centers under high fluoride loading. After 50 adsorption-regeneration cycles, the breakthrough capacity retention rate reaches 96%. Third, the closed loop formed by alkaline elution regeneration and dilute hydrochloric acid activation allows the zirconium sites to reversibly switch between the activated state, the fluorine-loaded state and the desorbed state. The fluorine in the eluent is recovered in the form of calcium fluoride and the filtrate is reused. The whole process does not introduce new impurities such as silicon, calcium, boron and organosilicon into the hydrochloric acid. It does not require distillation and can be operated continuously, making it suitable for reuse scenarios with strict requirements for fluorine. Attached Figure Description
[0010] Figure 1 This is a process flow diagram of the deep purification method for defluorination by adsorption of hydrochloric acid, a byproduct of the present invention.
[0011] Figure 2 The chemical structural formula of the phosphonic acid ligand used in this invention is shown below, wherein (I) is {1-hydroxy-2-[4-(2-hydroxy-2,2-bisphosphonoethyl)phenyl]-1-phosphonoethyl}phosphonic acid, (II) is {2-[3,5-bis(2-hydroxy-2,2-bisphosphonoethyl)phenyl]-1-hydroxy-1-phosphonoethyl}phosphonic acid, and (III) is {1-hydroxy-2-[4-(2-methylpropyl-2-yl)phenyl]-1-phosphonoethyl}phosphonic acid.
[0012] Figure 3 This is a schematic diagram illustrating the mechanism of the conversion of zirconium sites in the acid-resistant defluorination adsorption material of the present invention between the three stages of adsorption, elution regeneration and hydrochloric acid activation.
[0013] Figure 4 The breakthrough curves of Example 1 and Comparative Examples 1 to 3 under the same feeding conditions are shown, where (a) is the change of fluorine content at the outlet of the pre-column with the throughput, and (b) is the change of fluorine content at the outlet of the post-column of Example 1 with the throughput.
[0014] Figure 5 The curves show the changes in the penetration capacity retention rate of Examples 1, 4 to 6 and Comparative Examples 2 and 3 during multiple adsorption-regeneration cycles.
[0015] Figure 1 In the middle section: 1 is the pretreatment by-product hydrochloric acid storage tank, 2 is the feed pump, 3 is the heat exchanger, 4 is the first adsorption column, 5 is the second adsorption column, 6 is the switching valve group, 7 is the online fluoride monitoring unit, 7a is the automatic sampler, 7b is the dilution-buffer, 7c is the fluoride ion selective electrode, 8 is the deep fluoride removal hydrochloric acid storage tank, 9 is the regeneration unit, 9a is the water tank, 9b is the alkali tank, 9c is the activated hydrochloric acid tank, 9d is the gradient displacement hydrochloric acid tank, 10 is the eluent collection tank, 11 is the calcium salt precipitation reactor, 12 is the solid-liquid separator, 13 is the calcium fluoride, and 14 is the filtrate replenishment and reuse unit. Detailed Implementation
[0016] The present invention will be further described below with reference to the accompanying drawings and embodiments. The following embodiments are used to illustrate the present invention, but are not intended to limit the scope of the invention. Operations in the embodiments without specific conditions are performed according to conventional conditions in the art, and all raw materials and reagents used are commercially available analytical grade products unless otherwise specified. In the present invention, BV represents bed volume, and BV / h represents the bed volume passing through per hour; fluorine content is expressed as elemental fluorine; zirconium and phosphorus content are expressed as elements; unless otherwise specified, all percentage contents are mass fractions.
[0017] I. Raw materials and reagents.
[0018] The acid-resistant porous carrier used in this invention is commercially available macroporous polystyrene-divinylbenzene microspheres with a crosslinking degree of not less than 50%, a wet sieve particle size of 0.4~0.8 mm, and a specific surface area of 620 m² measured by nitrogen adsorption method. 2 / g, average pore size 9.5 nm, pore volume 0.95 cm³ 3 / g, before use, was rinsed sequentially with ethanol, 1 mol / L hydrochloric acid, and deionized water, and then vacuum dried at 60°C for 8 h. The zirconium source was zirconium oxychloride octahydrate (ZrOCl2·8H2O, CAS No. 13520-92-8). 1,4-phenylenediacetic acid (CAS No. 7325-46-4), phenyl-1,3,5-triacetic acid (CAS No. 4435-67-0), 4-tert-butylphenylacetic acid (CAS No. 32857-63-9), phosphorous acid (CAS No. 13598-36-2), phosphorus trichloride (CAS No. 7719-12-2), and methanesulfonic acid (CAS No. 75-75-2) used in the synthesis of the phosphonic acid ligands were all commercially available reagents. The 1-hydroxyethane-1,1-diphosphonic acid (HEDP, CAS No. 2809-21-4) used in the comparative examples was a 60% aqueous solution. The aminophosphonic acid chelating resin was a commercially available macroporous aminomethylphosphonic acid chelating resin (sodium form, total exchange capacity 1.7 mmol / mL). Sodium hydroxide, calcium chloride, ethanol, acetic acid, sodium acetate, etc., were all commercially available analytical grade reagents.
[0019] The by-product hydrochloric acid processed by this invention is hydrochloric acid produced by a fluorochemical plant and pretreated by precipitation. The following three types were used in the examples: By-product hydrochloric acid A was derived from the clear liquid after calcium chloride precipitation pretreatment and precision filtration of by-product hydrochloric acid from a difluorochloromethane plant. It contained 31.0% hydrogen chloride by mass, 85 mg / L fluorine, 45 mg / L calcium, 3.1 mg / L iron, 1.8 mg / L aluminum, 5.6 mg / L silicon, and 1.5 mg / L free chlorine. By-product hydrochloric acid B was derived from the clear liquid after siliceous material reaction precipitation pretreatment of by-product hydrochloric acid from a trifluoromethyl aromatics fluorination plant. It contained 28.2% hydrogen chloride by mass, 150 mg / L fluorine, 18 mg / L silicon, 6.0 mg / L iron, and 3.2 mg / L free chlorine. Byproduct hydrochloric acid C is derived from the clarified liquid after pretreatment with lime slurry precipitation of dilute hydrochloric acid from a fluorine-containing fine chemical plant. It contains 22.5% hydrogen chloride, 40 mg / L fluorine, 60 mg / L calcium, and 2.2 mg / L iron. All three byproduct hydrochloric acids are precisely filtered through a 5 μm filter element before entering the adsorption column, ensuring suspended solids do not exceed 5 mg / L and free chlorine does not exceed 5 mg / L.
[0020] II. Synthesis of phosphonic acid ligands.
[0021] Synthesis Example 1: Synthesis of Compound I, namely {1-hydroxy-2-[4-(2-hydroxy-2,2-diphosphonoethyl)phenyl]-1-phosphonoethyl}phosphonic acid. 66.6 g (0.343 mol) of 1,4-phenylenediacetic acid and 270 mL of methanesulfonic acid were added to a 2 L four-necked flask equipped with a mechanical stirrer, reflux condenser, constant-pressure dropping funnel, and tail gas absorption device. The mixture was heated to 60°C under nitrogen protection and stirred until the solid was completely dissolved. Then, 140.6 g (1.714 mol) of phosphorous acid was added and stirred until dissolved. The temperature was lowered to 20–25°C, and 235.4 g (1.714 mol) of phosphorus trichloride was added dropwise over 1 h, controlling the material temperature to not exceed 30°C during the addition. The tail gas was absorbed with sodium hydroxide solution. After the addition was complete, the temperature was raised to 65–70°C and the reaction was maintained for 20 h. The reaction solution was pale yellow and transparent. The reaction solution was cooled to 25°C and slowly added dropwise to 1.1 L of ice water under cooling. After the addition was complete, the mixture was refluxed for 6 h to complete hydrolysis. The solution was then cooled to 25°C, and 3.5 L of ethanol was added and stirred for 2 h. A white solid precipitated, which was filtered. The solid was washed twice with 300 mL of ethanol and dried under vacuum at 60°C for 12 h to obtain 100.3 g of a white hygroscopic powder, with a yield of 60.2%. The product was then subjected to… 31 A single peak at δ 18.9 ppm was measured by P nuclear magnetic resonance (D2O); 1 ¹H NMR (D₂O) measured δ 7.21 ppm (singlet, 4H, aromatic ring hydrogen) and δ 3.22 ppm (triplet, 4H, methylene hydrogen); electrospray mass spectrometry measured m / z 485.0 ([M−H]).− ), with molecular formula C 10 H 18 O 14 The P4 (relative molecular mass 486.1) is consistent; the measured phosphorus content is 25.3% (theoretical value 25.5%). 31 P has an NMR purity of 98.1%. The structure of compound I is as follows: Figure 2 As shown in (I).
[0022] Synthesis Example 2: Synthesis of Compound II, namely {2-[3,5-bis(2-hydroxy-2,2-diphosphonoethyl)phenyl]-1-hydroxy-1-phosphonoethyl}phosphonic acid. Using the same apparatus and procedures as in Synthesis Example 1, 33.2 g (0.132 mol) of benzene-1,3,5-triacetic acid, 135 mL of methanesulfonic acid, 81.0 g (0.988 mol) of phosphorous acid, and 135.7 g (0.988 mol) of phosphorus trichloride were added. The reaction mixture was kept at 65–70°C for 24 h. The reaction solution was then refluxed in 0.6 L of ice water for 6 h for hydrolysis. 2.0 L of ethanol was added to precipitate the product. After filtration, washing, and drying, 50.1 g of a white powder was obtained, with a yield of 55.0%. Product 31 A single peak at δ 18.7 ppm was measured by P nuclear magnetic resonance (D2O); 1 δ 7.15 ppm (single, 3H) and δ 3.18 ppm (triple, 6H) were measured by ¹H NMR; m / z 688.9 ([M−H]) was measured by electrospray mass spectrometry. − ), with molecular formula C 12 H 24 O 21 The value is consistent with P6 (relative molecular mass 690.1); the measured phosphorus content is 26.7% (theoretical value 26.9%). The structure of compound II is as follows. Figure 2 As shown in (II).
[0023] Synthesis Example 3: Synthesis of Compound III, namely {1-hydroxy-2-[4-(2-methylprop-2-yl)phenyl]-1-phosphonoethyl}phosphonic acid. Using the same apparatus and procedures as in Synthesis Example 1, 40.6 g (0.211 mol) of 4-tert-butylphenylacetic acid, 165 mL of methanesulfonic acid, 43.3 g (0.528 mol) of phosphorous acid, and 72.5 g (0.528 mol) of phosphorus trichloride were added. The reaction mixture was kept at 65–70°C for 18 h. The reaction solution was then refluxed dropwise into 0.7 L of ice water for 6 h for hydrolysis. The solution was concentrated under reduced pressure to approximately 150 mL, cooled to 5°C for crystallization for 4 h, filtered, and the solid was washed twice with cold water and dried under vacuum at 60°C for 12 h to obtain 50.0 g of white crystalline powder, with a yield of 70.0%. Product 31 A single peak at δ 19.4 ppm was measured by P nuclear magnetic resonance (D2O);1 ¹H NMR measurements showed δ 7.38 ppm (doublet, 2H), δ 7.22 ppm (doublet, 2H), δ 3.20 ppm (triplet, 2H), and δ 1.28 ppm (singlet, 9H); electrospray mass spectrometry measured m / z 337.1 ([M−H]). − ), with molecular formula C 12 H 20 The molecular weight (relative molecular mass) is consistent with O7P2 (338.2); the measured phosphorus content is 18.1% (theoretical value 18.3%). The structure of compound III is as follows. Figure 2 As shown in (III).
[0024] In the above synthetic reaction, the carboxylic acid is first converted to an acyl chloride or mixed anhydride in the phosphorus trichloride and phosphorous acid system. The phosphorous acid undergoes two nucleophilic additions to the carbonyl carbon via its H-phosphonic acid tautomer, generating a phosphonyl chloride and pyrophosphonic acid intermediate of 1-hydroxy-1,1-genomic bisphosphonic acid, which is then hydrolyzed to obtain free hydroxy-genomic bisphosphonic acid. Methanesulfonic acid is used as a solvent to maintain the homogeneity of the system and suppress side reactions. This type of reaction has mature industrial precedents. The feed amounts of the three compounds are all calculated from the mass of the target product based on its relative molecular mass, and those skilled in the art can scale it up proportionally.
[0025] III. Preparation of acid-resistant defluorination adsorption materials.
[0026] Preparation Example 1: Preparation of Adsorbent A1. 100 g of dried macroporous polystyrene-divinylbenzene microspheres were soaked in 300 mL of ethanol for 1 h to fully wet the pores, then drained. 40.0 g (0.124 mol) of zirconium oxychloride octahydrate was dissolved in 200 mL of a 1.0 mol / L hydrochloric acid solution (ethanol to water volume ratio 1:1), and the wetted microspheres were added. The mixture was shaken and soaked at 25°C for 4 h, then drained. 30.2 g (0.0621 mol) of compound I was dissolved in 250 mL of deionized water to prepare an aqueous solution of phosphonic acid ligands, with a zirconium to phosphonic acid group molar ratio of 1:2.0. The drained zirconium-loaded microspheres were added, and the mixture was reacted with slow stirring at 80°C for 12 h to allow the zirconic acid framework to form in situ within the microsphere pores, then drained. 500 mL of 4 mol / L hydrochloric acid was added to the microspheres, and the mixture was aged at 90°C for 24 h. After draining, the microspheres were rinsed with deionized water until the zirconium content in the washing solution was below 0.1 mg / L, using approximately 8 BV of water. The microspheres were then rinsed with 1 mol / L hydrochloric acid for 3 BV and stored in a wet state to obtain adsorbent material A1. Inductively coupled plasma atomic emission spectrometry (ICP-AES) analysis after digestion revealed that A1 contained 8.9% zirconium (dry basis) and 6.1% phosphorus, with a phosphorus to zirconium molar ratio of 2.02. The specific surface area was determined to be 385 m² / g by nitrogen adsorption. 2 / g; dry basis bulk density 0.51 g / mL, each liter of bed contains 45.4 g of zirconium, or 0.498 mol.
[0027] Preparation Example 2: Preparation of Adsorbent A2. The method of Preparation Example 1 was followed, except that the phosphonic acid ligand aqueous solution was prepared by dissolving 23.2 g (0.0477 mol) of compound I and 6.58 g (0.00954 mol) of compound II in 250 mL of deionized water. The molar ratio of compound II to compound I was 0.2:1, and the molar ratio of zirconium to the total amount of phosphonic acid groups was 1:2.0. The resulting adsorbent A2 had a zirconium mass fraction of 8.7%, a phosphorus mass fraction of 6.0%, a phosphorus to zirconium molar ratio of 2.05, and a specific surface area of 375 m². 2 / g, dry basis bulk density 0.52 g / mL.
[0028] Preparation Example 3: Preparation of Adsorbent A3. The material from Preparation Example 1, after aging and washing with water, was added to 300 mL of a 1 mol / L hydrochloric acid solution containing 2.10 g of Compound III (6.21 mmol, representing 5.0% of the zirconium content in the material). The solution was immersed at 40°C for 4 h to seal the adsorbent. After draining, the material was rinsed with deionized water for 3 BV, then rinsed again with 1 mol / L hydrochloric acid for 3 BV. The material was then stored in a humid state to obtain adsorbent A3. The mass fraction of zirconium in A3 was 8.8%, and the mass fraction of phosphorus was 6.3%.
[0029] Preparation Example 4: Preparation of Adsorbent Material A4. The material from Preparation Example 2, after aging and washing with water, was subjected to end-capping treatment with Compound III using the same method as in Preparation Example 3 to obtain adsorbent material A4. A4 contains 8.7% zirconium by mass, 6.2% phosphorus by mass, and has a specific surface area of 370 m². 2 / g, dry basis bulk density 0.52 g / mL, 45.2 g of zirconium per liter of bed, i.e., 0.496 mol. Characterization of A4: Fourier transform infrared spectrum in the range of 1040–1130 cm⁻¹. −1 A broadened P–O stretching vibration absorption band appears at this point, relative to the 950–1000 cm⁻¹ of the free ligand. −1 The shift in the absorption band indicates that the phosphonic acid group is coordinated with zirconium; 31 The solid-state NMR spectrum showed a broad peak at δ 24 ppm, with a low-field shift relative to the free ligand at δ 19 ppm, consistent with the characteristics of zirconium-coordinated phosphonates; X-ray photoelectron spectroscopy revealed Zr 3d 5 / 2The binding energy is 182.9 eV, and the P 2p binding energy is 133.4 eV. X-ray diffraction shows a broad diffraction peak at approximately 7.5° 2θ, corresponding to an interlayer spacing of approximately 1.18 nm, indicating that the framework has a short-range ordered layered structure. Scanning electron microscopy energy dispersive spectroscopy shows that zirconium and phosphorus are uniformly distributed on the cross-section of the microspheres, and the microspheres are spherical and intact.
[0030] Comparative Preparation Example 1: Preparation of Comparative Material C1. Following the method of Preparation Example 1, zirconium oxychloride was impregnated, but without the addition of phosphonic acid ligands. Instead, zirconium-loaded microspheres were immersed in 500 mL of a 5% (w / w) sodium hydroxide solution and treated at 25°C for 4 h, causing zirconium to precipitate in the pores as hydrated zirconium oxide. The microspheres were washed with water until neutral and then rinsed with 1 mol / L hydrochloric acid for 3 BV to obtain Comparative Material C1, with a zirconium mass fraction of 8.5%. Comparative Preparation Example 2: Preparation of Comparative Material C2. Commercially available aminomethylphosphonic acid chelating resin was converted to its hydrogen form with 1 mol / L hydrochloric acid and immersed in a 0.5 mol / L zirconium oxychloride solution (adjusted to pH 1.5 with hydrochloric acid) at 25°C with shaking for 24 h to load zirconium. The microspheres were washed with water until no zirconium was detected in the washings and then rinsed with 1 mol / L hydrochloric acid for 3 BV to obtain Comparative Material C2, with a zirconium mass fraction of 6.3% and a dry basis bulk density of 0.40 g / mL. Comparative Preparation Example 3: Preparation of Comparative Material C3. Prepared according to the method of Preparation Example 1, except that 42.6 g (0.124 mol, calculated as a 60% aqueous solution) of HEDP was used instead of compound I. The molar ratio of zirconium to phosphonic acid groups remained 1:2.0, resulting in Comparative Material C3 with a zirconium mass fraction of 8.6% and a phosphorus to zirconium molar ratio of 1.95. Comparative Preparation Example 4: Preparation of Comparative Materials C4a and C4b. Prepared according to the method of Preparation Example 1, except that the amount of compound I added was 48.3 g (0.0993 mol, zirconium to phosphonic acid group molar ratio of 1:3.2) and 18.1 g (0.0372 mol, zirconium to phosphonic acid group molar ratio of 1:1.2), respectively, resulting in Comparative Materials C4a (zirconium mass fraction 7.6%) and C4b (zirconium mass fraction 9.8%). Comparative Preparation Example 5: Preparation of Comparative Material C5. Prepared according to the method of Preparation Example 4, the only difference being that after the zirconic acid framework was generated in situ, it was not aged with 4 mol / L hydrochloric acid at 90°C, but directly washed with water and then capped to obtain the comparative material C5, which had a zirconium mass fraction of 9.3%.
[0031] IV. Adsorption and Defluorination System and Operation Mode.
[0032] like Figure 1As shown, the by-product hydrochloric acid adsorption and defluorination system of the present invention includes a pre-treatment by-product hydrochloric acid storage tank 1, a feed pump 2, a heat exchanger 3, a first adsorption column 4 and a second adsorption column 5 connected in series, a switching valve group 6, an online fluoride monitoring unit 7, a deep defluorination hydrochloric acid storage tank 8, a regeneration unit 9, an eluent collection tank 10, a calcium salt precipitation reactor 11, a solid-liquid separator 12, and a filtrate replenishment and reuse unit 14. The by-product hydrochloric acid, after precipitation pretreatment, is fed by the feed pump 2 and, after temperature adjustment by the heat exchanger 3, sequentially passes through the first adsorption column 4 (as a pre-adsorption column) and the second adsorption column 5 (as a post-adsorption column). The deep defluorination hydrochloric acid from the outlet of the post-adsorption column enters the deep defluorination hydrochloric acid storage tank 8. The online fluoride monitoring unit 7 consists of an automatic sampler 7a, a dilution-buffer 7b, and a fluoride ion selective electrode 7c. The automatic sampler 7a takes samples from the pre-column outlet at regular intervals. The sample is first diluted 25 times with deionized water in the dilution-buffer 7b to ensure that the hydrogen chloride concentration does not exceed 0.5 mol / L, and then one-tenth of the volume of 5 mol / L acetate-sodium acetate buffer (pre-adjusted with sodium hydroxide to make the pH of the mixed solution 5.0~5.5) is added. The fluoride content is measured by the fluoride ion selective electrode 7c, and the sampling cycle is 10 min. When the fluoride content at the pre-column outlet reaches the set threshold, or when the ratio of the amount of fluoride entering the pre-column to the amount of zirconium in the pre-column, calculated cumulatively from the feed flow rate and the inlet fluoride content, reaches 1.2:1 within the current adsorption cycle, the control system sends a command to the switching valve group 6 to switch the original post-column to the pre-column, and connects the regenerated adsorption column as the new post-column, while the original pre-column is disconnected and enters regeneration. The regeneration unit 9 sequentially uses deionized water from water tank 9a, alkaline solution containing sodium phosphonic acid ligands from alkaline solution tank 9b, deionized water from water tank 9a again, dilute hydrochloric acid from activated hydrochloric acid tank 9c, and 4-6 mol / L hydrochloric acid and deeply defluorinated hydrochloric acid from gradient displacement hydrochloric acid tank 9d to perform water displacement, alkaline elution regeneration, water washing, hydrochloric acid activation, and gradient displacement on the cut-out adsorption column. The eluent obtained from alkaline elution enters the eluent collection tank 10, reacts with calcium chloride in the calcium salt precipitation reactor 11 to produce calcium fluoride, and is separated by solid-liquid separator 12 to obtain calcium fluoride 13. The filtrate is replenished with sodium hydroxide in the filtrate replenishment and reuse unit 14 and then returned to alkaline solution tank 9b for recycling.
[0033] The adsorption columns used in the examples and comparative examples were jacketed glass columns lined with polyvinylidene fluoride (PVDF), with an inner diameter of 50 mm, a bed height of 500 mm, a bed volume of 1.0 L, and a bed height-to-diameter ratio of 10:1. The jacket was circulated with constant-temperature water to control the bed temperature. The adsorption column operated in a bottom-in, top-out manner, with the feed flow rate controlled by a metering pump. A sampling valve was installed after the column. The outlet of the pre-column was continuously monitored by an online fluorine monitoring unit 7, and the product acid from the outlet of the post-column was sampled every 20 BV and sent to the laboratory for analysis.
[0034] V. Testing methods.
[0035] The laboratory determination of fluoride content in hydrochloric acid was performed using ion chromatography: 1.00 mL of sample was diluted to 50 mL with deionized water, neutralized to pH 6-8 with sodium hydroxide solution, and injected. Fluoride ions were determined using an anion exchange separation column and a conductivity detector. The method detection limit was 0.1 mg / L (based on orthocyanin). When the fluoride content was higher than 5 mg / L, the fluoride ion-selective electrode method was also used. The sample was diluted 25 times, and one-tenth of a volume of 5 mol / L acetate-sodium acetate buffer was added to adjust the pH to 5.0-5.5. The potential was measured using a fluoride ion-selective electrode and a saturated calomel reference electrode. The fluoride content was calculated from a matrix-matched standard curve. The relative deviation between the two methods in the range of 5-200 mg / L did not exceed 3%. The contents of zirconium, phosphorus, calcium, iron, aluminum, and silicon in hydrochloric acid were determined using inductively coupled plasma atomic emission spectrometry (ICP-AES). The detection limit for zirconium was 0.005 mg / L. The mass fraction of hydrogen chloride was determined by acid-base titration according to GB / T 320-2006. The zirconium and phosphorus contents in the adsorbent material were determined by inductively coupled plasma atomic emission spectrometry (ICP-AES) after digestion with sulfuric acid and hydrogen peroxide. The breakthrough bed volume was defined as the cumulative bed volume that passed through when the fluorine content at the pre-column outlet reached a set threshold. The fluorine-zirconium molar ratio was calculated by accumulating the amount of fluorine entering the adsorption column based on the feed flow rate, inlet fluorine content, and running time, then dividing by the amount of zirconium in the adsorption column. The breakthrough capacity retention rate was defined as the ratio of the breakthrough bed volume in a given cycle to the breakthrough bed volume in the first cycle. The desorption rate was defined as the ratio of the total fluorine in the eluent obtained from a single alkaline elution to the total fluorine retained by the adsorption column during that adsorption cycle. The wear rate was defined as the percentage of fine particles passing through a 0.3 mm sieve after a specified number of cycles, relative to the total dry mass of the adsorbent material. The purity of calcium fluoride was determined according to the method specified in GB / T 5195.1-2017.
[0036] VI. Explanation of the range of process parameters.
[0037] Regarding the hydrogen chloride mass fraction and fluoride content of the by-product hydrochloric acid: The hydrogen chloride mass fraction of the by-product hydrochloric acid treated by this invention is adjusted within the range of 20% to 36%. Below 20%, hydrochloric acid itself is already a dilute acid and is generally not used for high-value reuse. Furthermore, the degree of dissociation of hydrogen fluoride increases with decreasing acidity. In this case, existing water treatment adsorbents are suitable, and the acid-resistant system of this invention is unnecessary. Above 36%, hydrochloric acid is close to the azeotropic and saturated region, and the escape of hydrogen chloride makes online monitoring, sampling, and dilution operations unstable. The fluoride content is adjusted within the range of 10 to 200 mg / L. Below 10 mg / L, precipitation pretreatment is sufficient, and the deep purification of this invention is unnecessary. Above 200 mg / L, the fluorine-zirconium molar ratio rapidly approaches the switching upper limit of 1.2:1 within a single adsorption cycle, resulting in a short permeable bed volume and frequent switching and regeneration. In this case, precipitation pretreatment should be strengthened first. The preferred feed fluoride content is 40 to 150 mg / L, at which point the single-cycle permeable bed volume is 44 to 156 BV, matching the switching and regeneration cycles.
[0038] Regarding the molar ratio of zirconium to phosphonic acid groups: This invention controls the molar ratio of zirconium to phosphonic acid groups to be 1:(1.6~2.4). When the number of phosphonic acid groups is less than 1.6, some zirconium is connected by zirconium-oxy-zirconium bridges or zirconium-hydroxy-zirconium bridges to form hydrated zirconium oxide aggregates. These bridges are protonated and depolymerized in concentrated hydrochloric acid, leading to zirconium loss, as confirmed by the results of comparative material C4b. When the number of phosphonic acid groups is more than 2.4, each zirconium is surrounded by more than four phosphorus and oxygen atoms, and the number of water or hydroxyl coordination sites that can be replaced by hydrogen fluoride is reduced to less than two, resulting in a decrease in penetration capacity, as confirmed by the results of comparative material C4a. The preferred molar ratio is 1:(1.9~2.1), at which point each zirconium is anchored by an average of four oxygen atoms from two phosphonic acid groups, and retains more than three open coordination sites. Example 1 shows optimal penetration capacity and zirconium retention.
[0039] Regarding the upper limit of the fluorine-zirconium molar ratio switching, it is 1.2:1. This invention uses the ratio of the cumulative amount of fluorine entering the adsorption column to the amount of zirconium in the column within the current adsorption cycle not exceeding 1.2:1 as one of the switching conditions: when this ratio exceeds 1.2:1, the average fluorine coordination number of the zirconium sites in the front section of the column approaches or exceeds 2, further leading to hydrogen fluoride substitution to generate ZrF4 and ZrF5. − In this type of species, the Zr–O–P bond of the zirconate skeleton is replaced by fluorine, causing zirconium to desorb into hydrochloric acid in the form of fluorozirconate ions. This was confirmed by the zirconium loss and capacity decay in Comparative Example 6. When the ratio is between 0.6 and 1.1, the adsorption capacity can be fully utilized while maintaining zero zirconium loss. The operations of Examples 1 to 7 were all within this range.
[0040] Regarding the concentration of the alkali solution and the activation concentration of hydrochloric acid: The alkali solution concentration should be adjusted within the range of 0.5~2 mol / L: below 0.5 mol / L, the replacement of fluorine by hydroxide ions is incomplete, and the desorption rate is less than 90%; above 2 mol / L, the hydrolysis of Zr–O–P bonds on the surface by hydroxide ions intensifies, leading to increased ligand loss. 1 mol / L is preferred. The activation concentration of hydrochloric acid should also be adjusted within the range of 0.5~2 mol / L: below 0.5 mol / L, the zirconium sites cannot be completely replaced by Zr–O… − Na + Zr–OH is converted into proton-activated Zr–OH2. + In the initial stage of re-operation, the fluoride content at the outlet is relatively high; when it exceeds 2 mol / L, the amount of activation solution and acid consumption increases without any additional benefit. 1 mol / L is preferred.
[0041] Regarding the preparation conditions of the adsorbent material: The reaction temperature of the phosphonic acid ligand aqueous solution with the zirconic acid microspheres is 60–95°C, and the reaction time is 6–24 h. When the temperature is below 60°C or the reaction time is less than 6 h, the zirconic acid framework is not fully formed, resulting in more free zirconium residue. When the temperature is above 95°C or the reaction time is longer than 24 h, the framework grows excessively at the pore openings, clogging the pores and reducing the effective zirconium content. The preferred reaction temperature is 80°C for 12 h. The curing process uses hydrochloric acid at a concentration of 3–6 mol / L, a temperature of 80–95°C, and a time of 12–48 h. The purpose of curing is to pre-dissolve the weakly anchored zirconium linked by zirconium-oxygen-zirconium bridges with a strong acid during the preparation stage and to promote the conversion of residual Zr–OH to Zr–O–P bonds. When the hydrochloric acid concentration is below 3 mol / L, the temperature is below 80°C, or the time is less than 12 h, the pre-dissolution is incomplete, resulting in high zirconium loss in the initial stage of use, as confirmed by the comparative material C5. When the hydrochloric acid concentration is above 6 mol / L, the temperature is above 95°C, or the time is longer than 48 h, the framework itself begins to slowly dissolve, increasing zirconium loss without any additional benefit. A 4 mol / L hydrochloric acid curing at 90°C for 24 h is preferred. Washing with water until the zirconium content in the washing solution is below 0.1 mg / L ensures that the zirconium content in the acid of the product after use is below 0.05 mg / L. The zirconium mass fraction in the material is 6%~12%: below 6%, the zirconium content per liter of bed is insufficient, resulting in a short penetration bed volume; above 12%, the framework is over-filled in the channels, increasing mass transfer resistance and making the microspheres fragile. Preferably, it is 8%~9%. The molar ratio of coligand compound II to compound I is (0.1~0.3):1: below 0.1, the three-connecting nodes are insufficient to crosslink the two-connected chain and layered framework into a three-dimensional network, resulting in limited improvement in swelling and fragmentation during cycling; above 0.3, the coordination saturation of zirconium at the nodes is too high, reducing open sites and decreasing capacity. Preferably, it is 0.2:1. The amount of compound III used for end-capping is 3%–10% of the zirconium content, the hydrochloric acid concentration is 0.5–2 mol / L, the temperature is 30–50°C, and the treatment time is 2–8 h. When the amount is less than 3%, the under-coordinated zirconium at the pore opening and grain edge is not completely chelated, resulting in insufficient end-capping effect. When the amount is greater than 10%, excess compound III enters the larger channels and occupies normal sites, leading to a decrease in capacity. The lower limits of hydrochloric acid concentration, temperature, and time ensure sufficient coordination between the end-capping ligand and the edge zirconium, while the upper limits prevent the re-dissolution of the matured framework. The preferred amount is 5%, 1 mol / L hydrochloric acid, and treatment at 40°C for 4 h.
[0042] Regarding adsorption operating conditions: Flow rate: 2~10 BV / h: Below 2 BV / h, equipment capacity is low; above 10 BV / h, residence time is insufficient. In concentrated hydrochloric acid with high proton activity, the substitution reaction of individual zirconium sites is inhibited, the mass transfer zone is lengthened, and breakthrough occurs prematurely. Temperature: 10~45°C: The substitution of hydrogen fluoride at zirconium sites is an exothermic process. Excessive temperature reduces equilibrium capacity and accelerates the slow hydrolysis of surface Zr–O–P bonds. Below 10°C, the reaction rate and acid viscosity lengthen the mass transfer zone. Optimal temperatures are 15~35°C and 4~8 BV / h. Bed height-to-diameter ratio is (4~12):1 to ensure the mass transfer zone length is much smaller than the bed height and to avoid excessive pressure drop. When operating a single column, the threshold is set to 0.5–1 mg / L. When operating a dual-column system in series, the threshold for the pre-column is 5%–10% of the inlet fluoride content. At this point, the pre-column has utilized most of its capacity while the outlet concentration of the post-column remains below 0.5 mg / L. A threshold below 5% results in insufficient utilization of the pre-column capacity, while a threshold above 10% overloads the post-column. The online monitoring dilution factor should ensure that the hydrogen chloride concentration does not exceed 0.5 mol / L, and that the acetate-sodium acetate buffer solution can adjust the solution to pH 5.0–5.5. At this pH, fluoride exists in the form of fluoride ions, and hydroxide interference is negligible, allowing the fluoride ion selective electrode to respond normally. The sampling cycle is 5–30 min. A cycle shorter than 5 min results in excessive sample and reagent consumption, while a cycle longer than 30 min leads to lag in penetration recognition.
[0043] Regarding regeneration and fluorine recovery conditions: The alkali dosage is 2–5 BV, the flow rate is 1–3 BV / h, and the temperature is 20–40°C. Desorption is incomplete when the dosage is below 2 BV or the flow rate is above 3 BV / h. A dosage above 5 BV dilutes the eluent, increasing the load on subsequent precipitation. Temperatures above 40°C exacerbate the hydrolysis of the framework by hydroxide ions. The concentration of sodium or potassium phosphonic acid ligands in the alkali solution is 0.2–2 mmol / L. Concentrations below 0.2 mmol / L are insufficient to reverse the hydrolysis equilibrium of the Zr–O–P bonds on the surface. Concentrations above 2 mmol / L increase the residue of ligands in the eluent and allow them to enter the calcium salt precipitation unit with the eluent. During calcium chloride precipitation, the molar ratio of calcium to fluoride is (0.55~0.8):1: . Below 0.55, calcium fluoride precipitation is incomplete, and residual fluoride in the filtrate is returned to the adsorption column with the recycled alkali solution. Above 0.8, excess calcium in the filtrate reacts with phosphonic acid ligand salts in the alkali solution to form calcium phosphonate, which is deposited in the column during regeneration, as confirmed by Comparative Example 7. The precipitation temperature is 40~60°C, and the time is 0.5~2 h to obtain easily filterable calcium fluoride crystals. The water volume for water replacement and water washing is 1~3 BV each, and the 4~6 mol / L hydrochloric acid used for gradient replacement and the hydrochloric acid used for deep defluorination are 1~2 BV each. Insufficient dosage will dilute the product acid with residual water and cause the bed temperature to rise due to the exothermic dilution; excessive dosage will not provide additional benefits.
[0044] VII. Examples
[0045] Example 1. The adsorbent material A4 obtained in Preparation Example 4 was packed into the first adsorption column 4 and the second adsorption column 5, respectively, with a bed volume of 1.0 L per column and a zirconium content of 0.496 mol. Byproduct hydrochloric acid A was used as feed, and the feed temperature was controlled at 25°C via heat exchanger 3. The feed flow rate was 5 BV / h, sequentially passing through the first adsorption column 4 (pre-column) and the second adsorption column 5 (post-column). The pre-column outlet was continuously monitored by an online fluorine monitoring unit 7 at 10-minute intervals, with a threshold set at 10% of the inlet fluorine content, i.e., 8.5 mg / L. Simultaneously, the amount of fluorine entering the pre-column was calculated by accumulating the feed flow rate and the inlet fluorine content, and the upper limit of its ratio to the amount of zirconium in the column was set at 1.2:1. The operating results are as follows: Figure 4 As shown, the fluorine content at the pre-column outlet remained below 1 mg / L for the first 60 BV, then gradually increased, reaching the set threshold of 8.5 mg / L at 79 BV. At this point, the cumulative fluorine entering the pre-column was 6.72 g (0.354 mol), and the fluorine-zirconium molar ratio was 0.71:1, which did not reach the upper limit of 1.2:1. The control system issued a switching command according to the outlet threshold condition. Throughout the adsorption cycle, the acid fluorine content of the product at the post-column outlet, determined by ion chromatography, was 0.2–0.4 mg / L, with an average of 0.3 mg / L. The zirconium content was 0.02 mg / L, the phosphorus content was 0.03 mg / L, and the hydrogen chloride mass fraction was 30.9%. The contents of other impurities such as iron and silicon remained unchanged compared to the feed, and no newly introduced impurities were detected. After the switch, the original post-column became the pre-column, and the regenerated third adsorption column was connected as the post-column, allowing the system to operate continuously.
[0046] The cut-off saturated adsorption column was regenerated according to the following steps: First, the hydrochloric acid in the column was replaced from top to bottom with 2 BV of deionized water at a flow rate of 2 BV / h; then, elution was carried out at 30°C with 3 BV of sodium hydroxide solution containing 1.0 mol / L sodium salt of compound I (prepared by neutralizing compound I with sodium hydroxide beforehand) at a flow rate of 2 BV / h, and the eluent was collected in eluent collection tank 10; then, it was washed with 2 BV of deionized water; then, it was activated at 25°C with 2 BV of 1.0 mol / L hydrochloric acid; finally, it was replaced sequentially with a gradient of 1 BV of 5 mol / L hydrochloric acid and 1 BV of deep defluorination hydrochloric acid for later use. The total eluent volume was 3.0 L, the fluoride content was 2.20 g / L, the total fluoride content was 6.6 g, and the desorption rate was 98.5%. 23.1 g of anhydrous calcium chloride (0.208 mol, with a calcium to fluoride molar ratio of 0.6:1) was added to the eluent, and the mixture was stirred at 50°C for 1 h. The mixture was filtered to obtain a calcium fluoride filter cake, which was washed with water and dried at 105°C to obtain 13.2 g of calcium fluoride with a purity of 96.5% and a fluoride recovery rate of 94%. The calcium content in the filtrate was 8 mg / L. Sodium hydroxide was added to bring the concentration to 1.0 mol / L, and the filtrate was returned to the alkali tank 9b as the alkali solution for the next regeneration.
[0047] The adsorbent material A4 was subjected to 50 adsorption-regeneration cycles following the above adsorption and regeneration steps. The breakthrough capacity retention rate for each cycle is as follows: Figure 5 As shown, the permeate bed volume in the 50th cycle was 76 BV, and the permeate capacity retention rate was 96%. Throughout the 50 cycles, the zirconium content of the product acid remained consistently between 0.015 and 0.03 mg / L, and the phosphorus content did not exceed 0.05 mg / L. The desorption rate in each cycle was 98%–99%. After 50 cycles, the wear rate of the adsorbent material was 0.4%, the microspheres remained intact, and the specific surface area was 362 m². 2 The zirconium mass fraction was 8.6% (g), showing no significant change compared to the fresh material. X-ray photoelectron spectroscopy analysis of the fluorine-loaded material after 50 cycles showed that the F 1s binding energy was 684.9 eV, consistent with the characteristic binding energy of the Zr–F bond. No signals of free fluoride ions or calcium fluoride were detected, indicating that fluorine was captured in the form of Zr–F bonds.
[0048] Example 2. Hydrochloric acid B, a byproduct, was used as feed with a hydrogen chloride mass fraction of 28.2% and a fluorine content of 150 mg / L. The feed temperature was 35°C, and the flow rate was 4 BV / h. The adsorbent material and adsorption column were the same as in Example 1. The pre-column threshold was set to 5% of the inlet fluorine content, i.e., 7.5 mg / L, and the upper limit of the fluorine-zirconium molar ratio was 1.2:1. The pre-column outlet reached the set threshold of 7.5 mg / L at 44 BV and then switched. The cumulative fluorine entering the pre-column was 6.60 g, i.e., 0.347 mol, with a fluorine-zirconium molar ratio of 0.70:1. The product acid at the post-column outlet had a fluorine content of 0.3~0.5 mg / L, a zirconium content of 0.03 mg / L, and a silicon content of 18 mg / L, the same as the feed, indicating that the fluorosilicate silicon remaining after pretreatment in the feed did not deposit inside the column. The regeneration conditions were the same as in Example 1. After 30 cycles, the breakthrough capacity retention rate was 95%, and the zirconium acid content in the product never exceeded 0.04 mg / L.
[0049] Example 3. Using byproduct hydrochloric acid C as feed, with a hydrogen chloride mass fraction of 22.5% and a fluorine content of 40 mg / L, the feed temperature was 15°C, and the flow rate was 8 BV / h. The adsorbent material and adsorption column were the same as in Example 1. The pre-column threshold was set to 10% of the inlet fluorine content, i.e., 4 mg / L. The pre-column outlet reached the set threshold at 156 BV and switched. The cumulative fluorine entering the pre-column was 6.24 g, i.e., 0.328 mol, with a fluorine-to-zirconium molar ratio of 0.66:1. The product acid at the post-column outlet had a fluorine content of 0.1–0.3 mg / L and a zirconium content of 0.01 mg / L. The 60 mg / L calcium in the feed remained unchanged in the product acid, indicating that divalent calcium ions did not interact with the zirconium sites. Regeneration conditions were the same as in Example 1, and the breakthrough capacity retention rate was 97% after 30 cycles.
[0050] Example 4. Adsorbent A1 obtained in Preparation Example 1 was used instead of A4, and the rest was the same as in Example 1. The pre-column outlet reached the set threshold of 8.5 mg / L at 68 BV, and the cumulative fluorine entering the pre-column was 5.78 g, or 0.304 mol, with a fluorine-zirconium molar ratio of 0.61:1. The fluorine content of the acid product at the post-column outlet was 0.3~0.6 mg / L, and the zirconium content was 0.10 mg / L. After 50 cycles, the breakthrough capacity retention rate was 88%, the attenuation rate was 1.5%, the average zirconium content of the acid product in the first 5 cycles was 0.10 mg / L, and in the 50th cycle it was 0.06 mg / L, still meeting the deep defluorination requirement of below 0.5 mg / L, but the zirconium loss and cycle stability were not as good as in Example 1.
[0051] Example 5. Adsorbent A2 obtained in Preparation Example 2 was used instead of A4, and the rest was the same as in Example 1. The pre-column outlet reached the set threshold at 74 BV, with a cumulative fluorine input of 6.29 g (0.331 mol) and a fluorine-zirconium molar ratio of 0.67:1. The post-column outlet product acid had a fluorine content of 0.2-0.5 mg / L and a zirconium content of 0.07 mg / L. After 50 cycles, the breakthrough capacity retention rate was 90%, and the attrition rate was 0.6%. Compared with Example 4, the three-connecting node introduced by compound II reduced the attrition rate from 1.5% to 0.6%, and increased the breakthrough bed volume from 68 BV to 74 BV.
[0052] Example 6. Adsorbent A3 obtained in Preparation Example 3 was used instead of A4, and the rest was the same as in Example 1. The pre-column outlet reached the set threshold at 71 BV, and the cumulative amount of fluorine entering the pre-column was 6.04 g, or 0.318 mol, with a fluorine-zirconium molar ratio of 0.64:1. The fluorine content of the product acid at the post-column outlet was 0.2~0.5 mg / L, and the zirconium content was 0.03 mg / L. After 50 cycles, the breakthrough capacity retention rate was 91%, and the attrition rate was 1.3%. Compared with Example 4, the end-capping treatment of compound III reduced the zirconium content in the product acid from 0.10 mg / L to 0.03 mg / L, increased the breakthrough capacity retention rate from 88% to 91%, while the improvement in the attrition rate was limited.
[0053] Example 7. Using byproduct hydrochloric acid B as feed, the adsorbent material and adsorption column were the same as in Example 1. The feed temperature was 35°C, and the flow rate was 4 BV / h. To investigate the operating status near the upper limit of the fluorine-zirconium molar ratio, the set threshold of the pre-column was increased to 50% of the inlet fluorine content, i.e., 75 mg / L, while the upper limit of the fluorine-zirconium molar ratio remained at 1.2:1. The pre-column outlet reached the set threshold of 75 mg / L at 68 BV and switched. The cumulative fluorine entering the pre-column was 10.2 g, i.e., 0.537 mol, and the fluorine-zirconium molar ratio was 1.08:1. Before switching, in the last 10 BV, the zirconium content at the pre-column outlet increased from 0.03 mg / L to 0.06 mg / L, and the phosphorus content increased from 0.03 mg / L to 0.08 mg / L. The fluorine content of the product acid at the post-column outlet was 0.4~0.7 mg / L. After the pre-column is regenerated under the conditions of Example 1, the volume of the through bed in the next cycle is 98% of that in the previous cycle, indicating that operating to a high fluorine load under the condition that the fluorine-zirconium molar ratio does not exceed 1.2:1 will not cause irreversible loss of zirconium sites.
[0054] 8. Comparative examples.
[0055] Comparative Example 1. Comparative material C1, i.e., hydrated zirconium oxide confined within macroporous polystyrene-divinylbenzene microspheres, was used instead of A4; the rest was the same as in Example 1. Upon initial feeding, significant zirconium dissolution was observed at the hydrochloric acid outlet of the pre-column, with an average zirconium content of 46 mg / L in the first 10 BV. The fluorine content at the pre-column outlet reached the set threshold of 8.5 mg / L at 9 BV, as shown in the breakthrough curve. Figure 4 As shown, the cumulative fluorine entering the pre-column was 0.77 g, or 0.040 mol, with a fluorine-to-zirconium molar ratio of 0.08:1. The fluorine content of the acid at the post-column outlet reached a maximum of 2.5 mg / L, which does not meet the requirements for deep defluorination. After three adsorption-regeneration cycles, the breakthrough capacity retention rate was only 30%, and the cumulative loss of zirconium accounted for 38% of the packing. This comparative example indicates that zirconium supported in the form of hydrated zirconium oxide aggregated with hydroxyl and oxygen bridges is rapidly lost due to proton depolymerization in hydrochloric acid with a hydrogen chloride mass fraction of 31%, and cannot serve as an active center for defluorination with concentrated hydrochloric acid.
[0056] Comparative Example 2. Comparative material C2, i.e., zirconium-loaded aminomethylphosphonic acid chelating resin, was used instead of A4. The amount of zirconium in the column was 0.276 mol, and the rest was the same as in Example 1. The fluorine content at the pre-column outlet reached the set threshold at 27 BV, with a cumulative fluorine input of 2.30 g (0.121 mol) and a fluorine-zirconium molar ratio of 0.44:1. During operation, the average zirconium content at the pre-column outlet was 3.2 mg / L, and the fluorine content in the acid at the post-column outlet was 0.8–1.6 mg / L. The resin exhibited a volume change of 18% between alkaline regeneration and hydrochloric acid activation, and after 10 cycles, the breakthrough capacity retention rate was 48%, and the wear rate was 4.5%. This comparative example shows that the commercial aminophosphonic acid chelating resin, with zirconium weakly coordinated between amino groups and single phosphonic acid groups, continuously loses its load in concentrated hydrochloric acid due to amino protonation and reversible dissociation of monodentate phosphonic acid. Furthermore, the resin repeatedly swells and shrinks under alternating acid and alkali conditions, failing to meet the requirements for continuous deep defluorination.
[0057] Comparative Example 3. Zirconic acid material C3, prepared by replacing compound I with HEDP, was used instead of A4. The amount of zirconium in the column was 0.481 mol, and the rest was the same as in Example 1. The fluorine content at the pre-column outlet reached the set threshold at 61 BV, with a cumulative fluorine content of 5.19 g (0.273 mol) entering the pre-column, resulting in a fluorine-zirconium molar ratio of 0.57:1. The average zirconium content at the pre-column outlet was 0.6 mg / L, and the fluorine content in the acid product at the post-column outlet was 0.4–0.9 mg / L. After 50 cycles, the breakthrough capacity retention rate was 62%, and the attenuation rate was 2.8%. HEDP is a small molecule with a single hydroxy bisphosphonic acid group. The zirconium in the framework formed with HEDP can only be bridged by phosphonic acid oxygen and lacks rigid organic spacer groups. The framework is in a loose granular aggregate state, gradually dissolving and fragmenting under 3–6 mol / L hydrochloric acid aging and repeated acid-base cycles. This comparative example shows that the bridging structure formed by the two hydroxy bisphosphonic acid groups separated by p-phenylene dimethylene groups in compound I is the structural basis for the long-term stability of the zirconium site in concentrated hydrochloric acid.
[0058] Comparative Example 4. Comparative materials C4a (molar ratio of zirconium to phosphonic acid groups of 1:3.2) and C4b (molar ratio of zirconium to phosphonic acid groups of 1:1.2) were used instead of A4, with the rest being the same as in Example 1. When C4a was used, the amount of zirconium in the column was 0.425 mol, the fluorine content at the pre-column outlet reached the set threshold at 23 BV, the cumulative fluorine entering the pre-column was 1.96 g, or 0.103 mol, the fluorine-zirconium molar ratio was 0.24:1, the zirconium content at the pre-column outlet was 0.02 mg / L, and the breakthrough capacity retention rate after 50 cycles was 95%, meaning the material was stable but the capacity was only one-third of that in Example 1. This is because the excessive phosphonic acid groups saturated the coordination sites of zirconium with phosphorus and oxygen atoms, leaving insufficient sites that could be replaced by hydrogen fluoride. When C4b was used, the amount of zirconium in the column was 0.548 mol. The fluorine content at the pre-column outlet reached the set threshold at 52 BV. The cumulative amount of fluorine entering the pre-column was 4.42 g, or 0.233 mol. The fluorine-zirconium molar ratio was 0.43:1. The zirconium content at the pre-column outlet was 8.5 mg / L on average in the first cycle. After 10 cycles, the breakthrough capacity retention rate was 55%. This is because when there are insufficient phosphonic acid groups, some zirconium is connected by zirconium oxyzirconium bridges. This part of zirconium is depolymerized and lost in concentrated hydrochloric acid.
[0059] Comparative Example 5. Comparative material C5 (material not cured with 3-6 mol / L hydrochloric acid) was used instead of A4. The amount of zirconium in the column was 0.520 mol, and the rest was the same as in Example 1. The fluorine content at the pre-column outlet reached the set threshold at 66 BV, with a cumulative fluorine content of 5.61 g (0.295 mol) entering the pre-column, resulting in a fluorine-to-zirconium molar ratio of 0.57:1. The zirconium content at the pre-column outlet averaged 12 mg / L within the first 20 BV, then decreased to 1.5 mg / L. The fluorine content in the product acid at the post-column outlet was 0.3-0.8 mg / L, but the zirconium content was 1.2-12 mg / L, indicating excessive zirconium in the product acid. After 20 cycles, the breakthrough capacity retention rate was 74%. This comparative example shows that if the weakly anchored zirconium remaining in the in-situ generated zirconium phosphonate framework is not pre-dissolved with strong acid during the preparation stage and converted into Zr–O–P linkages, it will be lost with the product acid after use, causing continuous capacity decay.
[0060] Comparative Example 6. Using byproduct hydrochloric acid B as feed, the adsorbent material, adsorption column, feed temperature, and flow rate were the same as in Example 7, but the switching conditions for the outlet threshold and the upper limit of the fluorine-zirconium molar ratio were removed. The pre-column was continuously fed up to 95 BV. At this point, the fluorine content at the pre-column outlet was the same as at the inlet, and the cumulative fluorine entering the pre-column was 14.3 g, or 0.750 mol, with a fluorine-zirconium molar ratio of 1.51:1. After running at 75 BV, the zirconium content at the pre-column outlet continuously increased from 0.05 mg / L, reaching 6.5 mg / L at 90-95 BV. The phosphorus content simultaneously increased to 4 mg / L, indicating that zirconium desorbed along with the ligand in the form of fluorozirconate. After regeneration of the pre-column under the conditions of Example 1, the permeate bed volume in the next cycle was only 71% of the previous cycle. The comparative example, compared with Example 7, shows that once the fluorine-zirconium molar ratio exceeds 1.2:1, the Zr–O–P bonds in the zirconic acid framework are replaced by fluorine, and the active centers are irreversibly lost. Therefore, using a fluorine-zirconium molar ratio of 1.2:1 as the upper limit for switching is a necessary condition for maintaining the regenerative cycle of the adsorbent material.
[0061] Comparative Example 7. Adsorbent A4 was run as in Example 1, with the only difference being the regeneration conditions. Firstly, the alkali solution was a 1.0 mol / L sodium hydroxide solution without the sodium salt of Compound I. The remaining regeneration steps were the same, and the phosphorus content in the eluent was 6 mg / L in each regeneration cycle. In Example 1, after deducting the added sodium ligand, the net increase in phosphorus content in the eluent was 0.8 mg / L. After 50 cycles, the breakthrough capacity retention rate was 89%. Secondly, the alkali solution contained 1.0 mmol / L sodium salt of Compound I, but the molar ratio of calcium to fluorine increased to 1.2:1 during calcium chloride precipitation. The calcium content in the filtrate was 620 mg / L. After replenishing the alkali, it was reused as the alkali solution. By the 15th cycle, the pressure drop of the adsorption column increased to 3.2 times the initial value, and the breakthrough capacity retention rate dropped to 80%. The material was taken out, and energy dispersive spectroscopy analysis showed a calcium mass fraction of 1.8%. X-ray diffraction detected diffraction peaks of calcium phosphonate, indicating that excess calcium reacted with the phosphonic acid ligand salt in the alkali solution to form calcium phosphonate, which was deposited inside the column. This comparative example shows that the sodium ligand in the alkaline solution inhibits the hydrolysis of the Zr–O–P bond on the surface through mass action, while the upper limit of the molar ratio of calcium to fluorine of 0.8:1 avoids the deposition of calcium phosphonate. Together, they ensure the long-term stability of the regenerated closed loop.
[0062] IX. Summary and Analysis of Test Data
[0063] The main operating data of each embodiment and comparative example under the same or corresponding feeding conditions are summarized in Table 1.
[0064] Table 1 Summary of operational data for the examples and comparative examples
[0065] serial number Adsorbent materials Feeding Penetration bed volume / BV Fluorine-zirconium molar ratio during switching Product acid and fluoride content (mg / L) Zirconium content of the product (mg / L) Loop count Penetration Capacity Retention Rate / % Wear rate / % Example 1 A4 A 79 0.71 0.2~0.4 0.02 50 96 0.4 Example 2 A4 B 44 0.70 0.3~0.5 0.03 30 95 — Example 3 A4 C 156 0.66 0.1~0.3 0.01 30 97 — Example 4 A1 A 68 0.61 0.3~0.6 0.10 50 88 1.5 Example 5 A2 A 74 0.67 0.2~0.5 0.07 50 90 0.6 Example 6 A3 A 71 0.64 0.2~0.5 0.03 50 91 1.3 Example 7 A4 B 68 1.08 0.4~0.7 0.03~0.06 2 98 — Comparative Example 1 C1 A 9 0.08 Maximum 2.5 46 3 30 — Comparative Example 2 C2 A 27 0.44 0.8~1.6 3.2 10 48 4.5 Comparative Example 3 C3 A 61 0.57 0.4~0.9 0.6 50 62 2.8 Comparative Example 4 C4a A 23 0.24 0.2~0.4 0.02 50 95 — Comparative Example 4 C4b A 52 0.43 0.3~0.7 8.5 10 55 — Comparative Example 5 C5 A 66 0.57 0.3~0.8 1.2~12 20 74 — Comparative Example 6 A4 B 95 (Not switched) 1.51 — Maximum 6.5 2 71 — Comparative Example 7 A4 A 79 0.71 0.2~0.5 0.02 50 / 15 89 / 80 —
[0066] The zirconium acid content in Table 1 is the average value of the pre-column or post-column outlet during the first cycle. The zirconium content of C4b in Comparative Examples 1 and 4, and Comparative Examples 5 and 6 are given as the zirconium content at the pre-column outlet. The number of cycles and the breakthrough capacity retention rate of Comparative Example 7 correspond to its two regeneration conditions, respectively.
[0067] The following points can be analyzed from Table 1. First, regarding the anchoring method of the active center, hydrated zirconium oxide (Comparative Example 1), which also uses zirconium as the active center and is confined to macroporous polystyrene-divinylbenzene microspheres, breaks through at 9 BV and loses 38% of the zirconium in hydrochloric acid with a hydrogen chloride mass fraction of 31%. Zirconium loaded with commercial aminophosphonic acid chelating resin (Comparative Example 2) breaks through at 27 BV and continues to lose at a rate of 3.2 mg / L. The zirconic acid skeleton formed by HEDP with a single hydroxy bisphosphonic acid group (Comparative Example 3) breaks through at 61 BV and retains only 62% of its capacity after 50 cycles. The zirconic acid skeleton formed by bridging with compound I (Example 4) breaks through at 68 BV, retains 88% of its capacity after 50 cycles, and loses 0.10 mg / L of zirconium. The difference among the four lies not in zirconium itself, but in the protonation immunity of the bonds between zirconium and the framework: the zirconium-oxy-zirconium bridge and the amine coordination are protonated and broken in concentrated hydrochloric acid; the framework formed by monodentate phosphonic acid and a single geminiphosphonic acid group lacks bridging and gradually dissolves in acid; only geminiphosphonic acid groups bridged by rigid organic spacer groups can anchor zirconium in a non-protonable Zr–O–P bond network for a long time. This result contradicts the conventional understanding in the field that zirconium-based adsorbents are limited to aqueous systems with pH 2–7, proving that the failure of fluoride removal adsorption in concentrated hydrochloric acid stems from the anchoring mechanism rather than the form in which fluoride exists.
[0068] Second, regarding the molar ratio of zirconium to phosphonic acid groups, in Comparative Example 4, the material with an excess of phosphonic acid groups (1:3.2) was stable but had a breakthrough bed volume of only 23 BV, while the material with insufficient phosphonic acid groups (1:1.2) had a breakthrough bed volume of 52 BV but a zirconium loss of 8.5 mg / L. Only Example 4, with a ratio of 1:2.0, achieved both a breakthrough bed volume of 68 BV and a zirconium loss of 0.10 mg / L. This ratio determines the average number of phosphorus and oxygen atoms anchored to each zirconium atom and the number of coordination sites that can be replaced by hydrogen fluoride. It represents the balance between anchoring stability and the number of open sites, and the range of 1:(1.6~2.4) is precisely the interval of this balance point.
[0069] Third, regarding the effects and synergistic effects of compounds II and III, using adsorbent A1 from Example 4 as a baseline, the capacity loss after 50 cycles was 12%, compared to 10% in Example 5 (which only introduced compound II), 9% in Example 6 (which only introduced compound III), and 4% in Example 1 (which introduced both). If the effects of the two compounds were independent, the capacity loss when introduced simultaneously should be 12% minus the 2% improvement brought by compound II alone, minus the 3% improvement brought by compound III alone, which is 7%. However, the measured value of 4% is 3 percentage points lower than the expected sum, meaning that the improvement from introducing both compounds simultaneously is 8 percentage points, which is more than 1.6 times the sum of the individual improvements of 5 percentage points. Regarding the zirconium content of the product, A1 is 0.10 mg / L, compound II alone is 0.07 mg / L, and compound III alone is 0.03 mg / L. If the effects of the two are independent, the zirconium content when introduced simultaneously should be 0.10 mg / L multiplied by 0.7 and then by 0.3, which is 0.021 mg / L. The measured value of 0.02 mg / L is comparable to this. The permeable bed volume increased from 68 BV to 79 BV, which is higher than the sum of the individual increases of the two compounds, i.e., 68 BV + 6 BV + 3 BV = 77 BV. The above nonlinear synergistic effect stems from the complementarity of the two compounds' positions: compound II, as a three-connector node, improves the connectivity within the framework, forming a three-dimensional network within the channels and reducing the amount of under-matched zirconium at the grain edges; compound III, through volume exclusion, can only reach the pore openings and grain edges, transforming the residual under-matched zirconium into tridentate chelate non-leaching sites. When compound II has reduced the total number of edge sites, the same amount of compound III can more completely cover the remaining edge sites. The capping efficiency increases nonlinearly with the reduction of the number of edge sites. Therefore, the stability improvement when both are present exceeds the sum of their individual contributions.
[0070] Fourth, regarding operational control, Example 7 and Comparative Example 6, under the same materials and feed conditions, showed a 98% and 71% difference in post-regeneration capacity only due to whether or not the upper limit of the fluorine-zirconium molar ratio of 1.2:1 was applied. This indicates that the upper limit is not a negligible safety margin, but a necessary control condition determined by the fluorine-zirconate generation threshold. Comparative Example 7 demonstrates that the ligand sodium salt in the alkali solution and the upper limit of the calcium-fluorine molar ratio jointly determine the stability of the regeneration closed loop. Examples 2 and 3 show that within the range of hydrogen chloride mass fraction of 22.5%~31.0%, fluorine content of 40~150 mg / L, temperature of 15~35°C, and flow rate of 4~8 BV / h, the present invention can control the acid-fluorine content of the product below 0.5 mg / L and maintain the zirconium content below 0.05 mg / L, and the coexisting components such as calcium, silicon, and iron in the feed do not affect operation.
[0071] The mechanism of action of this invention can be combined with Figure 3This invention is explained from four levels: molecular structure, microstructure, macroscopic operation, and application effects. At the molecular level, in hydrochloric acid with a hydrogen chloride mass fraction of 20%–36%, the dissociation constant of hydrogen fluoride is extremely small, and fluoride exists as undissociated HF molecules, without exchangeable fluoride ions. Tetravalent zirconium is a hard acid, and fluoride ions are the hardest base. The primary complexation constant of tetravalent zirconium with fluoride is more than eight orders of magnitude higher than that with chloride ions. Chloride ions cannot enter the inner coordination layer of tetravalent zirconium in aqueous media and can only form external ion pairs. Therefore, the capture of fluoride by the zirconium sites in this invention is not anion exchange, but rather a substitution reaction of HF molecules on proton-activated zirconium sites: in media with a pH less than 0, the aqueous ligands on the zirconium sites react with the hydroxyl ligands in a Zr–OH2 reaction. + The zirconium center exists in a form that makes it an electrophilically activated center. The HF molecule nucleophilically substitutes the zirconium center with its fluorine atom, forming a Zr–F bond and releasing H3O. + ,like Figure 3 The process from activated sites to fluorinated sites is illustrated in the diagram. This reaction does not require fluoride ions and is not subject to chloride ion competition; the driving force of the reaction comes from the fact that the stability of the Zr–F bond is much higher than that of the Zr–OH2 coordination bond. Because the high proton activity in concentrated hydrochloric acid inhibits the substitution equilibrium of individual sites, deep removal requires zirconium sites to have high density, openness, and mutual isolation. This is precisely why this invention uses a zirconium to phosphonic acid group molar ratio of 1:(1.6~2.4) to ensure that each zirconium retains more than three open coordination sites, uses bridging ligands to avoid zirconium-oxygen-zirconium bridge saturation, and uses tandem dual columns and appropriate flow rates and bed height-to-diameter ratios to ensure residence time.
[0072] Regarding anchoring stability, the Zr–O–P bond formed between the phosphonic acid group and tetravalent zirconium is fundamental to the existence of the active center in concentrated hydrochloric acid. Both zirconium phosphate and zirconium phosphonate can be synthesized in concentrated hydrochloric acid and concentrated phosphoric acid and reflux without dissolving. This is because the basicity is strongly suppressed after the oxygen atom of the phosphonic acid is coordinated to the tetravalent zirconium, and the protonation energy is significantly lower than that of the zirconium hydroxyl bridge. Each hydroxyl bisphosphonic acid group of compound I forms a six-membered chelate ring and two five-membered chelate rings with the same zirconium through the oxygen atoms of the two phosphonic acid groups and the oxygen atom of the α-hydroxyl group. The chelate groups at both ends are connected to adjacent zirconium bridges through rigid p-phenylenediethylene spacers, so that the zirconiums are connected in the manner of Zr–O–P–C–C6H4–C–P–O–Zr rather than by zirconium oxyzirconium bridges. Conversely, zirconium in hydrated zirconium oxide aggregates via hydroxyl and oxygen bridges. These bridges are protonated and broken at pH less than 0, depolymerizing into soluble zirconium oxychloride species. This is the reason for the rapid loss of zirconium in Comparative Example 1. In commercial aminophosphonic acid resin, zirconium is weakly coordinated with only one phosphonic acid group and one protonated amino group, and its monodentate anchoring reversibly dissociates in concentrated hydrochloric acid. This is the reason for the continuous loss of zirconium in Comparative Example 2. After the zirconic acid framework is generated in situ within the pores, it is cured with 3-6 mol / L hydrochloric acid at 80-95°C. Its function is to pre-dissolve the weakly anchored zirconium still connected by zirconium oxychloride bridges under more stringent conditions than the operating medium during the preparation stage, and to promote the conversion of residual Zr–OH to Zr–O–P linkages, so that the material after use is in a state of zero zirconium loss. The results of Comparative Example 5 illustrate the necessity of the curing step.
[0073] Regarding fluorine loading and switching control, as the fluorine loading increases, the fluorine coordination number at a single zirconium site increases from 1 to 2 or 3. When the fluorine-zirconium molar ratio exceeds 1.2:1, ZrF4 and ZrF5 are generated at the front-end sites within the column. − In zirconium species, the affinity of fluorine for zirconium causes fluorine to replace the Zr–O–P bond, leading to the desorption of zirconium along with its ligands in the form of fluorozirconate. This process is consistent with the known chemical behavior of zirconium phosphonate decomposing into fluorozirconic acid in high-concentration hydrofluoric acid. Therefore, this invention employs a dual-threshold switching mechanism, using an outlet fluorine content threshold and an upper limit for the fluorine-zirconium molar ratio. The former ensures the fluorine content of the product acid, while the latter prevents zirconium sites from entering the fluorozirconate formation region. The comparison between Example 7 and Comparative Example 6 confirms the criticality of this upper limit. This also explains why this invention is placed after precipitation pretreatment: only when the feed fluorine content is controlled below 200 mg / L can the fluorine-zirconium molar ratio be controlled within a reasonable through-bed volume.
[0074] At the regeneration level, the substitution of fluorine by hydroxide ions in the alkaline solution (Zr–F + OH) − → Zr–OH + F − This is driven by the fact that zirconium has a higher affinity for hydroxyl groups than for fluorine. Under conditions of a large excess of hydroxide ions (0.5–2 mol / L), fluorine is quantitatively desorbed, such as… Figure 3 The process from fluorine-loaded sites to desorbed sites is shown in the diagram. Simultaneously, hydroxide ions slowly hydrolyze the Zr–O–P bonds at the pore openings and grain edges, causing phosphonic acid ligands to enter the eluent as sodium salts. In this invention, 0.2–2 mmol / L of compound I sodium salt is added to the alkaline solution, reversing this hydrolysis equilibrium through mass action. The hydrolyzed surface sites are re-anchored during regeneration. The reduction of ligand loss from 6 mg / L to 0.8 mg / L in Comparative Example 7 confirms this self-repairing effect. Subsequent activation with dilute hydrochloric acid causes the desorbed Zr–O… − Na + Zr–OH is reprotonated to form Zr–OH2. + The activated sites, such as Figure 3 As shown in the process of returning from the desorbed state site to the activated state site, the zirconium site thus reversibly cycles between the three states. Gradient displacement avoids the dilution exothermic reaction and product acid dilution when the adsorption column is directly exposed to concentrated hydrochloric acid after aqueous phase regeneration, while the upper limit of the calcium to fluorine molar ratio prevents the formation and deposition of calcium phosphonate in the recycled alkali solution within the column.
[0075] At the microstructural level, the zirconic phosphonic acid framework is confined within the pores of macroporous polystyrene-divinylbenzene microspheres. The polystyrene-divinylbenzene framework does not contain any groups that can be protonated or hydrolyzed in concentrated hydrochloric acid, providing the zirconic phosphonic acid framework with dimensionally stable mechanical support and fluid channels. Compound II, as a triple-connecting node, crosslinks the chain-like and layered frameworks formed by the bridging of compound I into a three-dimensional network, which inhibits the swelling and fragmentation of the framework during acid-base cycles. Compound III, due to the presence of a sterically hindered 4-tert-butylphenyl group, has a molecular size that allows it to reach only the pore openings and grain edges and not the interior of the framework. This transforms the undercoordinated zirconium at these positions, which are anchored only by a single phosphonic acid oxygen, into tridentate chelated zirconium. At the same time, a hydrophobic microenvironment is formed at the pore openings to slow down water-mediated Zr–O–P bond hydrolysis, while the open zirconium sites inside the framework remain unaffected. The three ligands respectively perform the functions of bridging and anchoring, network crosslinking and edge sealing. In Example 1, they together enable the adsorbent material to maintain 96% penetration capacity, 0.4% wear rate and 0.02 mg / L zirconium loss after 50 cycles.
[0076] At the macroscopic operation and application level, this invention transforms the aforementioned site chemistry into a continuously operating process: a series dual-column system allows the pre-column to fully utilize its capacity while the post-column ensures that the acid-fluoride content of the product is below 0.5 mg / L; online monitoring converts hydrogen fluoride in concentrated hydrochloric acid, which cannot be directly measured, into fluoride ions that can be measured by a fluoride ion selective electrode through dilution and buffering; and a closed-loop regeneration system recovers fluoride in the form of calcium fluoride and recycles the alkali solution. Compared with precipitation methods that consume silicon materials and rely on distillation, extraction methods that introduce organosilicon reagents, and alumina adsorption methods that can only be used in the gas phase, this invention does not introduce any new impurities into hydrochloric acid, the adsorbent material is regenerable and recyclable, and the energy consumption is only for pumping and heating the regenerated solution. The deeply defluorinated hydrochloric acid can be directly used in the preparation of pharmaceutical and food-grade chloride salts, the pretreatment of electronic-grade hydrochloric acid raw materials, and metal refining and surface treatment, as well as other scenarios with strict requirements for fluoride.
[0077] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A deep purification method for defluorination by adsorption of byproduct hydrochloric acid, characterized in that, Includes the following steps: S1. The by-product hydrochloric acid, after precipitation pretreatment, is passed through an adsorption column filled with acid-resistant defluorination adsorption material to obtain deeply defluorinated hydrochloric acid from the outlet of the adsorption column; the by-product hydrochloric acid has a hydrogen chloride mass fraction of 20%~36% and a fluorine content of 10~200 mg / L; the acid-resistant defluorination adsorption material consists of an acid-resistant porous support and a zirconic acid skeleton confined within the pores of the acid-resistant porous support, the zirconic acid skeleton is formed by the coordination of tetravalent zirconium and phosphonic acid ligands through Zr–O–P bonds, the molar ratio of zirconium to phosphonic acid groups in the phosphonic acid ligand is 1:(1.6~2.4), and the phosphonic acid ligand is {1-hydroxy-2-[4-(2-hydroxy-2,2-diphosphonoethyl)phenyl]-1-phosphonoethyl}phosphonic acid; S2. Monitor the fluorine content at the outlet of the adsorption column online. When the outlet fluorine content reaches a set threshold, or when the ratio of the cumulative amount of fluorine entering the adsorption column to the amount of zirconium in the adsorption column during the current adsorption cycle reaches 1.2:1, switch the by-product hydrochloric acid to another adsorption column. S3. The adsorption column after switching is sequentially subjected to water replacement, alkaline elution and regeneration, water washing and hydrochloric acid activation, and then used again in step S1; the alkaline solution is a sodium hydroxide solution or potassium hydroxide solution with a concentration of 0.5~2 mol / L, and the concentration of hydrochloric acid used for hydrochloric acid activation is 0.5~2 mol / L.
2. The deep purification method for defluorination by adsorption of by-product hydrochloric acid according to claim 1, characterized in that, The preparation method of the acid-resistant defluorination adsorbent material includes: immersing the acid-resistant porous carrier in a hydrochloric acid-ethanol solution containing zirconium oxychloride and then draining it, followed by immersion in an aqueous solution of the phosphonic acid ligand, and reacting at 60-95°C for 6-24 h to allow the zirconic acid framework to be generated in situ within the pores; then aging it in 3-6 mol / L hydrochloric acid at 80-95°C for 12-48 h, and washing it with water until the zirconium content in the washing solution is less than 0.1 mg / L; the acid-resistant porous carrier is macroporous polystyrene-divinylbenzene microspheres, and the mass fraction of zirconium in the acid-resistant defluorination adsorbent material is 6%-12%.
3. The deep purification method for defluorination by adsorption of by-product hydrochloric acid according to claim 2, characterized in that, The aqueous solution of the phosphonic acid ligand further contains {2-[3,5-bis(2-hydroxy-2,2-diphosphonoethyl)phenyl]-1-hydroxy-1-phosphonoethyl}phosphonic acid as a co-ligand, wherein the molar ratio of {2-[3,5-bis(2-hydroxy-2,2-diphosphonoethyl)phenyl]-1-hydroxy-1-phosphonoethyl}phosphonic acid to {1-hydroxy-2-[4-(2-hydroxy-2,2-diphosphonoethyl)phenyl]-1-phosphonoethyl}phosphonic acid is (0.1~0.3):1, and the molar ratio of zirconium to the total amount of phosphonic acid groups is 1:(1.6~2.4).
4. The deep purification method for adsorbing and removing fluoride from by-product hydrochloric acid according to claim 2 or 3, characterized in that, The acid-resistant defluorination adsorbent material, after aging, is further subjected to end-capping treatment: it is immersed in a 0.5~2 mol / L hydrochloric acid solution containing {1-hydroxy-2-[4-(2-methylprop-2-yl)phenyl]-1-phosphonoethyl}phosphonic acid and treated at 30~50°C for 2~8 h. The amount of {1-hydroxy-2-[4-(2-methylprop-2-yl)phenyl]-1-phosphonoethyl}phosphonic acid is 3%~10% of the molar amount of zirconium in the acid-resistant defluorination adsorbent material.
5. The deep purification method for defluorination by adsorption of by-product hydrochloric acid according to claim 1, characterized in that, In step S1, the flow rate of the by-product hydrochloric acid through the adsorption column is 2~10 BV / h, the temperature is 10~45°C, and the height-to-diameter ratio of the adsorption column is (4~12):1; in step S2, the set threshold is 0.5~1 mg / L.
6. The deep purification method for defluorination by adsorption of by-product hydrochloric acid according to claim 1, characterized in that, The adsorption column consists of at least two adsorption columns connected in series. The by-product hydrochloric acid passes through the pre-column and the post-column in sequence, and the deeply defluorinated hydrochloric acid is obtained from the outlet of the post-column. In step S2, the outlet of the pre-column is monitored online, and the set threshold of the outlet of the pre-column is 5% to 10% of the inlet fluorine content. When switching, the post-column is changed to the pre-column, and the regenerated adsorption column is connected as the new post-column.
7. The deep purification method for defluorination by adsorption of by-product hydrochloric acid according to claim 1, characterized in that, The online monitoring in step S2 is as follows: automatic sampling is performed at the outlet of the adsorption column, the sample is diluted with water to a concentration of no more than 0.5 mol / L, the pH is adjusted to 5.0~5.5 with an acetate-sodium acetate buffer solution, and the fluoride content is determined using a fluoride ion selective electrode. The sampling cycle is 5~30 min.
8. The deep purification method for defluorination by adsorption of by-product hydrochloric acid according to claim 1, characterized in that, In step S3, the amount of alkali used for elution and regeneration is 2-5 BV, the flow rate is 1-3 BV / h, and the temperature is 20-40°C; the alkali also contains sodium or potassium salt of {1-hydroxy-2-[4-(2-hydroxy-2,2-diphosphonoethyl)phenyl]-1-phosphonoethyl}phosphonic acid at a concentration of 0.2-2 mmol / L.
9. The deep purification method for defluorination by adsorption of by-product hydrochloric acid according to claim 8, characterized in that, Calcium chloride is added to the eluent obtained by elution and regeneration with the alkaline solution. The molar ratio of calcium to fluorine in the eluent is (0.55~0.8):
1. The mixture is reacted at 40~60°C for 0.5~2 h. Solid-liquid separation is performed to obtain calcium fluoride and filtrate. Sodium hydroxide or potassium hydroxide is added to the filtrate to a concentration of 0.5~2 mol / L, and the filtrate is then reused as the alkaline solution.
10. The deep purification method for defluorination by adsorption of by-product hydrochloric acid according to claim 1, characterized in that, In step S3, the water volume for water replacement and water washing is 1~3 BV each; after the hydrochloric acid is activated, it is replaced by hydrochloric acid with a concentration of 4~6 mol / L and the deep defluorination hydrochloric acid, each for 1~2 BV, and then used again in step S1.
Citation Information
Patent Citations
Preparation method of zirconium-loaded zeolite used for removing fluorine
CN101773816B
Synthesis method of fluoride ion adsorption resin
CN102641730B
Method for purifying hydrogen chloride
CN105377751A
Defluorination method of acidic aqueous solution containing hydrofluoric acid
CN106927423A
Method for separating and recycling mixed acid of hydrofluoric acid and hydrochloric acid
CN114436216A